Computer systems for determination of pressure distribution in the hip joint articular surface - Stankovski, Vlado (Radiology and oncology (Ljubljana), 2001)
Background. In this work, we describe the computer systems Viprecox and ActiveContours that are used in the process of realistic estimation of some biomechanical parameters of the hip joint, including the maximal value of the stress in the hip joint p max. The computer system Active Contours uses standard anteroposterior radiographs of the whole pelvis and both hips for itscalculations and Viprecox in its kernel uses a relatively simple three-dimensional mathematical model of stress distribution in the hip-joint articular surface which has been extensively elsewhere (e.g. Iglič 1996). Material and methods. Both state-of-the-art computer systems were tested by analysing the calculated values of p max for 81 patients (37 males and 44 females). Conclusions. In this way we prove that the described computer systems can be used for the determination of the contact stress distribution from standard AP radiographs.
Keywords: Biomechanics; biomehanika; Diagnosis, computer-assisted; Hip joint; kolčni sklep; Radiography; Stress, mechanical; tlak; Weight-bearing